The Opportunities and Threats of Coastal Development: An MPR Roundtable Discussion - Anderson, Paul (Maine Policy Review, 2000)
In May 2000, nine discussants—each with a unique perspective on coastal development—convened to explore changes occurring on the Maine coast, whether those changes are consistent with what Maine people want, and what looming issues invite further debate and creative problem solving. Their discussion spanned a range of sensitive issues including aquaculture development, the displacement of traditional economies, the effects of development on coastal wildlife populations, and the reality of diminishing public access to the coast. All agreed that with vision and careful planning we have an opportunity to shape the future of the Maine coast, but the jury is out as to whose vision and whose planning will prevail.